Physiological and transcriptome analysis of sex-specific responses to cadmium stress in poplars - Meihua Liu; Sumei Wu; Yigang Song; Mengjiao Shi; Lita Yi (Ecotoxicology and Environmental Safety)
Soil cadmium (Cd) pollution is a serious ecological problem worldwide. Understanding Cd-detoxification mechanisms in woody plants will help to evaluate their tolerance ability and phytoremediation potential to Cd-polluted soils. This study investigated the growth, physiochemistry, Cd distribution, and transcriptome sequencing of male and female poplars under three Cd levels (0, 50, and 100 mg·kg−1). The results showed that Cd stress significantly inhibited the growth of aboveground parts. Over 70 % of the Cd was distributed in the cell wall fraction of roots, stems, and leaves, with the majority accumulating in the roots. Poplars can conjugate Cd with phytochelatins to reduce Cd damage, which is more evident in males than females. The antioxidant defense system of females is more effective than that of males at reducing the damage from Cd. Females demonstrated a stronger Cd-regulation ability than males under the 100 mg·kg−1 Cd treatment. Sex-specific responses to Cd were associated with differential gene expression. Under Cd stress, the genes related to oxidation-reduction processes, antioxidant enzyme activity and defense mechanisms, cell wall synthesis, and glutathione metabolism were mainly enriched and upregulated in females, whereas in males, genes related to photosynthesis and photosynthetic pigment biosynthesis were mainly enriched and downregulated, indicating greater damage to the photosynthetic system than in females. Our study provides novel insights into the mechanisms responding to Cd tolerance in poplars. Further studies should be carried out to assess the impact of soil Cd pollution on the wood quality of poplars.